Estudos ecológicos dos peixes da bacia do rio Jequitinhonha - Andrade Neto, Francisco Ricardo de (2018)
This thesis deals with the ecology of freshwater fishes from the Jequitinhonha river basin. It was written by me and nine co-authors. I have divided it into three independent chapters, written and formatted according to the journals for which they were or will be submitted. In the first chapter we’ve investigated the distribution of freshwater fish richness along the elevational gradient in the upper Jequitinhonha river basin. Data revealed a mid-elevational peak in richness, which suggested the mid domain effect as an explanation. However, we saw evidence that species were not randomly distributed and therefore refuted this theory as well as the Rapoport’s rule. In the second chapter we’ve assessed for the first time, grazing by Serrasalmus brandtii upon netted fishes outside its natural range. We observed higher grazing proportions in samples from sites where S. brandtii was the dominant species in relation to sites where it was recorded as present and sites where it was absent. S. brandtii grazed preferentially on caudal fins from larger fish and avoided mutilating conspecifics. The number of species being preferentially grazed increased as the abundance of S. brandtii also increases. Chapter three deals with fish movement. We tagged and tracked three species of Loricariid fishes in a tributary from the Jequitinhonha river. Fishes exhibited small home range sizes (less than 700 m) and showed specific habitat requirements. The study river ceased flowing at least twice during the study, which concerned us about the future of the species Delturus brevis. These fishes relied on cobbles and fast flowing waters, two hydraulic features typical from the riverine areas that dried first. The recurrence of severe draughts in the next decades can lead to the extinction of this species in higher order tributaries from the Jequitinhonha river.